(untitled) - Hemsworth, Chris; Hiddleston, Tom; Pearson, Eric; Blanchett, Cate; 1969-; Waititi, Taika; Goldblum, Jeff; 1952-; Kyle, Craig; Feige, Kevin; Thompson, Tessa; 1983-; et al. ([United States], 2018)
Thor is imprisoned on the other side of the universe and finds himself in a race against time to get back to Asgard to stop Ragnarok, the destruction of his homeworld and the end of Asgardian civilization, at the hands of an all- powerful new threat, the ruthless Hela.
Keywords: Thor; (Norse deity); Drama; Drama; Mythology, Norse; Adventure and adventurers; Drama; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Action and adventure films; Fantasy films; Feature films